Similarity Model Test on the Spatiotemporal Evolution Law of Deformation and Failure of Surrounding Rock-Induced Caving in Multi-Mined-Out Areas - Fengyu Ren; Yanjun Zhou; Rongxing He; Jianli Cao; Kaihua Zou (Advances in Civil Engineering)
Taking the deep mined-out areas of Paishanlou Gold Mine as the research object, we designed the indoor similar physical model test and used VIC-3D and resistance pressure sensors to record the vertical stress and strain of the model during the test. And based on the results of digital image correlation (DIC) analysis, we deeply analyzed the deformation and failure characteristics of the surrounding rock in the process of goaf caving. At the same time, the failure mechanism of surrounding rock mass and the law of temporal and spatial evolution during the excavation process of pillars between the mined-out areas were studied. According to the characteristics of the caving process, it can be divided into three stages: initial caving in a small range at the arch angle, continuous vault collapse, and instantaneous huge caving of the roof. Before the occurrence of instantaneous large caving at the top, the phenomenon of sudden increase of caving arch curvature appears. Based on the monitoring results, it can also be seen that the deformation of overlying rock mass is most affected by the span of the cavity, and the vertical strain is inversely proportional to the depth. The rock mass stress and strain caused by the excavation of isolation pillars between adjacent two goafs have an obvious time delay phenomenon. The time delay effect of the strain is proportional to the span of the cavity; conversely, it is inversely proportional to the span of the cavity. Specifically, throughout the experiment, the subsidence of the target area of the test model is larger in the middle and smaller on both sides; simultaneously, the upper part is high, and the lower part is low. However, the variation of the stress value shows the characteristics of higher on both sides and lower on the middle area and higher on the upper part and lower on the lower part. To sum up, the experimental results show that the caving process can be predicted and effectively controlled manually, and a new treatment method can be provided for the control and prevention of the large caving and mining subsidence damage in the goaf combined with the field monitoring method.